2022
DOI: 10.30684/etj.2022.134576.1240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Field on the Performance of Solar Distillers: A Review Study

Abstract:  A complete survey on the factors that affect the performance of solar pyramid stills is explained.  Specific categorization of these factors is suggested.  Solar radiation is the strongest affecting parameter on the pyramid solar distiller performance.  Promising future scopes of work on the pyramid solar still is suggested.Due to the rising demand for treated water, the enhancement of potable water yield technologies, such as traditional solar distillers, is a pressing concern. Solar desalination is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Maintaining a substantial temperature difference between the water and the cooler glass cover has also been found to be beneficial [46]. Other Researchers has shown that magnetic fields have a substantial impact on water evaporation rates [47][48][49][50][51]. Consequently, the application of magnetic fields stands out as one of the most influential and contemporary techniques for enhancing the productivity of solar stills [52].…”
Section: Solar Stills Productivitymentioning
confidence: 99%
“…Maintaining a substantial temperature difference between the water and the cooler glass cover has also been found to be beneficial [46]. Other Researchers has shown that magnetic fields have a substantial impact on water evaporation rates [47][48][49][50][51]. Consequently, the application of magnetic fields stands out as one of the most influential and contemporary techniques for enhancing the productivity of solar stills [52].…”
Section: Solar Stills Productivitymentioning
confidence: 99%
“…The amount of water produced by a basin area in a day is commonly used to express the performance of solar stills [18,19]. The productivity of a distiller depends on a number of elements, which can be categorized into three components: meteorological or climate, operational, and design parameters [20,21].…”
Section: Solar Stills Productivitymentioning
confidence: 99%